Understanding on the big data:beyond the data management and analytics - Aoying ZHOU (大数据)
Big data is still a buzzword，and more and more people are talking about it with various kinds of different explanations.Based on writer’s understanding，the big data，big data strategy and “internet plus” initiative will be discussed here.The database philosophy was revisited，for understanding the development of data management is meaningful to catch the good opportunities in big data era.Moreover，from the point of view of a senior IT professional，the development paradigm for IT has been shifted in the past decade.The change was described，and three systems and their development and deployment were presented.A new concept，sharing database，was proposed to catch up the notion behind the block chain.